The Effect of the Principal's Leadership Effectiveness on Teacher Performance at SMK Negeri 1 Pantai Cermin - Haloho, Ronald Hervin; Simare-mare, Aman (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
SMK Negeri 1 Pantai Cermin, the Principal plays an important role in shaping policy, fostering a positive organizational culture, and offering strategic support to teaching staff. It is important to dig deep to understand the significant influence of principal leadership on teacher performance. This article will examine how effective leadership can foster a work environment that motivates and empowers teachers, ultimately improving the quality of education in schools. The main focus of this study is to assess the impact of the principal's leadership effectiveness on teacher performance at SMK Negeri 1 Pantai Cermin. Quantitative research methods will be used to achieve this goal. The process of quantitative research involves the utilization of numerical data to acquire knowledge and analyze information. Data collection methods in this type of research include questionnaires and documentation studies. The findings of this study show that the principal's leadership style has an impact on improving teacher performance. The effectiveness of a teacher's performance is determined by how well the principal displays the success of the school in its management. This is supported by an R square adjust value of 0.232 which shows that the principal's leadership style accounts for 23.2% of the variation in teacher performance. The remaining 76.8% was influenced by other variables that were not studied in this study, such as teacher compensation, teaching materials, teaching methods, curriculum readiness, school facilities and infrastructure.